Trial by Google: Judicial Notice in the Information Age - Bellin, Jeffrey (2014)
This Article presents a theory of judicial notice for the information age. It argues that the ease of accessing factual data on the Internet allows judges and litigants to expand the use of judicial notice in ways that raise significant concerns about admissibility, reliability, and fair process. State and federal courts are already applying the surprisingly pliant judicial notice rules to bring websites ranging from Google Maps to Wikipedia into the courtroom, and these decisions will only increase in frequency in coming years. This rapidly emerging judicial phenomenon is notable for its ad hoc and conclusory nature—attributes that have the potential to undermine the integrity of the factfinding process. The theory proposed here, which is the first attempt to conceptualize judicial notice in the information age, remedies these potential failings by setting forth both an analytical framework for decision, as well as a process for how courts should memorialize rulings on the propriety of taking judicial notice of Internet sources to allow meaningful review